2019
DOI: 10.1002/jccs.201900464
|View full text |Cite
|
Sign up to set email alerts
|

Amido PNP complexes of iridium: Synthesis and catalytic olefin and alkyne hydrogenation

Abstract: In situ lithiation of HN(o‐C6H4PPh2)2 (H[1a]) or HN(o‐C6H4PiPr2)2 (H[1b]) with nBuLi in THF at −35°C followed by addition of [Ir(μ‐Cl)(COD)]2 (COD = 1,5‐cyclooctadiene) in toluene at −35°C generates 5‐coordinate [1a]Ir(η4‐COD) (2a) or 4‐coordinate [1b]Ir(η2‐COD) (2b), respectively. Oxidative addition of N‐H in H[1b] to [Ir(μ‐Cl)(COD)]2 affords square pyramidal [1b]Ir(H)(Cl) (3b). Metathetical reaction of 3b with LiBHEt3 in the presence of 1 atm of H2 in toluene produces [1b]Ir(H)2 (4b). Both 2a and 4b are acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…These atoms, however, exhibit one instead of two resonances in its 1 H NMR spectrum. This result implies the insufficient steric size of [PyImN] − , reminiscent of what was found for [Me‐NP]AlEt 2 [27], [PNN]AlEt 2 [28], and [Ph‐PNP]AlEt 2 [29] but contrasting with two well‐resolved resonances observed for the H α atoms in [ i Pr‐NP]AlEt 2 [27] and [ i Pr‐PNP]AlEt 2 [29] whose corresponding chelating ligands are sterically more demanding [36–41].…”
Section: Resultsmentioning
confidence: 99%
“…These atoms, however, exhibit one instead of two resonances in its 1 H NMR spectrum. This result implies the insufficient steric size of [PyImN] − , reminiscent of what was found for [Me‐NP]AlEt 2 [27], [PNN]AlEt 2 [28], and [Ph‐PNP]AlEt 2 [29] but contrasting with two well‐resolved resonances observed for the H α atoms in [ i Pr‐NP]AlEt 2 [27] and [ i Pr‐PNP]AlEt 2 [29] whose corresponding chelating ligands are sterically more demanding [36–41].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the solution structures deduced from NMR spectroscopy, X-ray studies of these trimethylplatinum­(IV) complexes (Figure and Table ) revealed them to be distorted octahedral species having facial and meridional configurations. The [R-PNP]­M configuration in fac -[Ph-PNP]­PtMe 3 and fac -[ i Pr-PNP]­PtMe 3 is similar to that in fac -[Ph-PNP]­Ir­(η 4 -COD) but different from that in the majority of known PNP pincer complexes. ,, The mer -PtMe 3 configuration in mer -[Ph-PNP]­PtMe 3 and mer -[ i Pr-PNP]­PtMe 3 is unique in view of the popular fac -PtMe 3 core − ,− ,, in six-coordinate trimethylplatinum­(IV) complexes. Diagnostically, two of the methyl ligands in mer -[Ph-PNP]­PtMe 3 and mer -[ i Pr-PNP]­PtMe 3 are trans-disposed, having C–Pt–C angles of 178.1(2)° and 176.1(4)°, respectively.…”
mentioning
confidence: 90%
“…We are interested in reaction chemistry employing amido phosphine complexes. [22][23][24][25][26] Whereas [1a]NiCl and [1b]NiCl are catalytically active for Kumada couplings [20] and [1a]PdCl is active for Heck, [27] Suzuki, [28] and Sonogashira couplings, [29] [1a]PtMe and [1b]NiH are capable of arene C-H bond cleavage at room temperature in the presence of Lewis acids. [30,31] In an effort to expand the reaction chemistry of group 10 complexes of amido PNP, [32,33] we aim in this contribution to demonstrate the synthetic possibilities of a series of organopalladium and organoplatinum complexes of 1a and 1b and evaluate their compatibilities in catalytic Kumada couplings, particularly alkyl that contains β-hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%